Digital Literacy Based on Islamic Values to Improve Risk Perception and Critical Thinking among Muslim Adolescents - Suryani, Suryani; Asyraf, M. Fahmi Aufar; Mustofa, Ali; Muntafi, Muhammad Syifaul; M. Fahmi Aufar, M. Fahmi Aufar (Psikis : Jurnal Psikologi Islami, 2024)
Risk perception and critical thinking have become the two important cognitive skills for adolescents to possess in order to prevent risky online behavior such as spreading fake news. These skills are related to digital literacy and can be improved through training. However, most of the existing literature is in digital literacy training, online risk perception, and critical thinking by using correlational approach and conventional digital literacy training. For this reason, this research aimed to integrate Islamic values into digital training to improve risk perception and critical thinking skills among Muslim adolescents. This study hypothesized that digital literacy based on Islamic values can improve adolescents risk perception and critical thinking skills. To test this hypothesis, a pre-test post-test within experimental research design involving 112 Muslim adolescents in Surabaya was conducted. The participants were provided with digital literacy training which was embedded with Islamic values in four training sessions. The risk perception and critical thinking scale were used to measure each dependent variable. The results of data analysis using the paired sample t-test showed that there were significant differences in the scores of risk perception and critical thinking skills before and after training. Thus, the hypotheses in this study were accepted. The practical implications of the results of this study are also discussed.